(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Shobha De a prominent current writers and columnists in Indian English writing. She has turns into the image of featuring alternate points of view of women’s opportunity and freedom. She imagines additional conjugal undertakings of women as the stroke to break the conventional and good qualities in the public eye. Shobha Rajadhyaksha is a notable writer by the name of Shobha De in the domain of Indian English tale. Shobha is a talented author with phenomenal capacity to talk about extremely touchy parts of human life carefully. The manner in which she portrays every single part of human relationship when all is said in done and man-women relationship specifically, is sublime. Shobha varies from other Indian women authors writing in English. She is an author who has faith in extremely blunt portrayal of occurrences and total kindness. The present paper is an investigation of Shobha De’s first novel Socialite Evenings. De considers the additional conjugal issues of women as the stroke to break the customary and good qualities in the public eye. Socialite Evenings is about the adventure of a conspicuous Bombay socialite Karuna, from a white collar class young women to an independent women. Making a women’s activist methodology, the novel gives us the image of the minimization of the Indian women because of their spouses. Socialite Evenings is a novel that exhibits the establishments of family and marriage existing in the affluent class of the Indian culture. This depiction is genuine, being an inside story, on the grounds that the storyteller herself has a place with this class. Socialite Evenings is a sentimental story, suffused with women’s activist qualities. A continuing topic in the novel is the picture of new women, scan for character and selfhood.